2014
DOI: 10.1063/1.4902831
|View full text |Cite
|
Sign up to set email alerts
|

High spin polarization in CoFeMnGe equiatomic quaternary Heusler alloy

Abstract: We report the structure, magnetic property and spin polarization of CoFeMnGe equiatomic quaternary Heusler alloy. The alloy was found to exist in the L2 1 structure with considerable amount of DO 3 disorder. Thermal analysis result indicated the Curie temperature is about 711K without any other phase transformation up to melting temperature. The magnetization value was close to that predicted by the Slater-Pauling curve. Current spin polarization of P = 0.70 ± 0.1 was deduced using point contact Andreev reflec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…Bainsla et al [7,8] at 5 K were obtained for CoFeMnSi and CoFeMnGe respectively by Alijani et al [45]. The difference between the MS values for CoFeMnSi could be attributed to the large structural disorder observed by Bainsla et al [8,46].…”
Section: H Mnnicusb Alloymentioning
confidence: 82%
See 4 more Smart Citations
“…Bainsla et al [7,8] at 5 K were obtained for CoFeMnSi and CoFeMnGe respectively by Alijani et al [45]. The difference between the MS values for CoFeMnSi could be attributed to the large structural disorder observed by Bainsla et al [8,46].…”
Section: H Mnnicusb Alloymentioning
confidence: 82%
“…To further investigate the crystal structure of CoFeMnZ (Z = Si and Ge) alloys, Bainsla et al [7,8,46] performed EXAFS measurements [46] and found large structural disorder in the case of CoFeMnSi, while CoFeMnGe was found to exist in well ordered Y-phase. Room temperature 57 Fe Mössbauer analysis also revealed a large structural disorder (DO3) for…”
Section: A Cofemnz (Z = Al Ga Si and Ge) Alloysmentioning
confidence: 99%
See 3 more Smart Citations